A Moment of Glory? Richard Wagner, Heavy Metal and Film Music – An Investigation (KULT_online, 2010)
The focus of Michael Custodis' study is how versatile the traces of classical music in popular music styles (rock music respectively) can be. Sound and detailed analyses of a musical and sociological nature go hand-in-hand with a higher-level perspective. This perspective centres on the thesis of diversification of 20th century music and also functions as parenthesis for the investigation of the five case studies. Custodis is able to show that the much-touted end of so called 'classical' music is in no way in sight. The highly diversified use of this music is most notably reflected in the different popular music cultures.